Demokrasi dan Politik Islam dalam Pesrspektif Siyasah Dusturiyah - Burhan Hakim, Ahmad; Satryo Pringgo Sejati (HOKI : Journal of Islamic Family Law, 2024)
Reformation is a new chapter in political and social dynamics in Indonesia. The implementation of democracy in Indonesia cannot be separated from this major event. So with elections as the basis for implementing democracy, Indonesia is able to carry out this safely and in a controlled manner. So it is natural that Indonesia is a country with the world's largest Muslim population and is able to implement democracy well. Despite the fact that many countries with Muslim majority populations in the world have not been able to implement this. Deliberation is one of the important values ​​in Islam that operates and is in accordance with Islamic politics and siyasah dusturiyah as part of the administration of Islamic politics itself. Islam itself in concept and value will indeed go hand in hand with democracy which we consider to be the most ideal political system and ideology at this time. Islam and democracy also uphold justice as well as Pancasila. The methodology we use is descriptive qualitative and uses a research library to make it easier for us to conduct research. So it was found that democracy, Islamic politics from the perspective of siyasah dusturiyah is something that is in accordance with and does not conflict with Islam itself which loves peace and justice.